(untitled) (SAARC Journal of Agriculture, 2023)
Poor germination percentage and non-uniform seedling emergence and establishment are major causes of low rice yield in water-deficit arid ecosystems. A seed priming study with a low concentration of MoP, DAP, urea, vitamin C, ZnSO4, sucrose, NaCl, and hydro priming was conducted to assess the seed germination, seedling emergence, establishment, and seedling growth of the spring rice variety Hardinath-1. The experiment was conducted using a completely randomized design with three replications. Two test sets of experiments were carried out using blotting paper rolls and separate sand trays. Germination was observed at intervals of 24 hours up to 7 days, and germination and growth parameters were monitored. The results showed that germination (88.67%) and seedling emergence (88.67%) were high in vitamin C at 7 days after sowing (DAS). Germination energy (81%), germination speed (91.78%), and vigor index (91.78) were higher with seed priming of MoP. The lowest germination (56.44%) was observed with the priming of urea. At 30 DAS, the longest shoot length (19.93 cm) and longest root length (11.79 cm) were observed with the priming of ZnSO4. The highest seedling fresh weight (0.75 g) and dry weight (0.16 g), the highest number of leaves (3.57), and the longest leaf length (11.97 cm) were found with the priming of MoP, NaCl, and ZnSO4, respectively. However, the lowest seedling growth parameters were observed in the control priming. The overall results revealed that seed priming with MoP is an effective tool to enhance the germination percentage and seedling establishment of rice. SAARC J. Agric., 21(2): 81-93 (2023)